Rancang Bangun Alat Penanam Dan Pemupuk Jagung (Zea mays) Tipe Tugal Semi Mekanis Yang Ergonomis - Sugiana, I Wayan; Gunadnya, Ida Bagus Putu; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 5 No 1 (2017): maret, 2017)
Tujuan dari penelitian adalah untuk mendapatkan rancangan alat penanam dan pemupuk jagung yang mampu meringankan pekerjaan petani dalam budidaya jagung khususnya melakukan penanaman dan pemupukan dalam sekali proses kerja. Metode yang digunakan dalam penelitian adalah membuat prototipe alat penanam dan pemupuk jagung tipe tugal semi mekanis yang dilakukan pengujian pada lahan 100 m2 tanpa olah tanah dengan kondisi digenangi 2-3 hari sebelum tanam pada jarak tanam 25 cm dalam barisan dan 75 cm antar barisan. Hasil dari pengujian menunjukan bahwa rata-rata keluaran benih jagung dan pupuk untuk setiap lubang tanam adalah 2 benih dan 31-40 gram pupuk dengan tingkat keberhasilan 86,88 % dan 95 %, kapasitas lapang efektif 0,0122 ha/jam, kapasitas lapang teoritis 0,0135 ha/jam dan kecepatan jalan penanaman 12 lubang/menit. The purpose of this research was to get a prototype of a maize planters and fertilizer that can simplify work of farmers in the cultivation of maize, especially planting and fertilizing in one work process. The method used in this research is to create a prototype of a planter and corn fertilizer semi-mechanical that tested on 100 m2 of land no-tillage with flooded conditions 2-3 days before planting at a spacing of 25 cm in a row and 75 cm between rows. The results of the test show that the average output of corn was 2 seed to each hole and 31-40 grams fertilizer with a success rate of 86,88 % and 95 %, effective field capacity 0,0122 ha/hour, theoretical field capacity 0,0135 ha/hour and the speed of planting was 12 hole/minute. The purpose of this research was to get a prototype of a maize planters and fertilizer that can simplify work of farmers in the cultivation of maize, especially planting and fertilizing in one work process. The method used in this research is to create a prototype of a planter and corn fertilizer semi-mechanical that tested on 100 m 2 of land no-tillage with flooded conditions 2-3 days before planting at a spacing of 25 cm in a row and 75 cm between rows. The results of the test show that the average output of corn was 2 seed to each hole and 31-40 grams fertilizer with a success rate of 86,88 % and 95 %, effective field capacity 0,0122 ha/hour, theoretical field capacity 0,0135 ha/hour and the speed of planting was 12 hole/minute.
Keywords: Semi mekanis., alat Tanam., Pemupuk., Jagung., Pupuk.